Molecular design of recyclable thermosetting polyimide and its composite with excellent mechanical and tribological properties - Xiaoyue Wang; Zenghui Yang; Tingmei Wang; Qihua Wang; Xinrui Zhang; Song Li (Friction)
Abstract Recyclability of thermosetting polymers and their composites is a challenge for alleviating environmental pollution and resource waste. In this study, solvent-recyclable thermosetting polyimide (PI) and its composite were successfully synthesized. The tensile strength, elongation at break, and Young’s modulus of PI are 108.70 ± 7.29 MPa, 19.35% ± 3.89%, and 2336.42 ± 128.00 MPa, respectively. The addition of reduced graphene oxide (RGO) not only enhances the mechanical properties of PI but also endows it with excellent tribological properties. The PI illustrates a high recycling efficiency of 94.15%, but the recycled composite exhibits inferior mechanical properties. The recycling and utilization of PI and its composite are realized through imine bonds (–C=N), which provides new guidance for solving the problem of environmental pollution and resource waste and is potential application in the field of sustainable tribology.